Detrimental role of IL-33/ST2 pathway sustaining a chronic eosinophil-dependent Th2 inflammatory response, tissue damage and parasite burden during Toxocara canis infection in mice - Leal-Silva, Thaís; Vieira-Santos, Flaviane; Oliveira, Fabrício Marcus Silva; Padrão, Luiza de Lima Silva; Kraemer, Lucas; da Paixão Matias, Pablo Hemanoel; de Almeida Lopes, Camila; Loiola Ruas, Ana Cristina; de Azevedo, Isabella Carvalho; Nogueira, Denise Silva; Rachid, Milene Alvarenga; Caliari, Marcelo Vidigal; et al. (PLOS Neglected Tropical Diseases, 2021)
Author summary Toxocariasis is a neglected disease caused by Toxocara canis, which has 19% worldwide seroprevalence, and is associated with socioeconomic, geographic and environmental factors. Humans become infected by accidental ingestion of T. canis eggs present in contaminated food, water or soil. After ingestion, the larvae hatch in the intestine and can reach various tissues such as liver, lung and brain. Helminth infections usually trigger a Th2 immune response in the host, by releasing cytokines such as IL-4, IL-5, IL-13 and IL-33. IL-33 is an alarmin that binds to the ST2 receptor, and some studies have observed an increase in this cytokine in toxocariasis, however there are no studies regarding the IL-33/ST2 role in this infection. Thus, we evaluated the influence of this pathway by analyzing immunological and pathophysiological aspects in T. canis-infected mice. Our results demonstrated that the IL-33/ST2 pathway is related to parasite burden on the liver and brain and also increases the number of eosinophils in the blood and tissues. In addition, it involved with the pulmonary immune response and granulomas with impact in lung function. In conclusion, the IL-33/ST2 pathway governs the host susceptibility to T. canis in mice.